Program Peningkatan Status Kesehatan Lansia Melalui Senam Hipertensi di Banjarmasin - Anastasi Maratning; Ermeisi Er Unja; Aulia Rahman; Oktovin Oktovin (Jurnal Informasi Pengabdian Masyarakat, 2024)
The high incidence of hypertension is influenced by various factors, one of which is the activity factor. Physical activity can show a reduced risk of death in people with hypertension. Efforts that can be made for people with hypertension to lower blood pressure can be done one of them with hypertension exercises. This community service activity was carried out once, namely on Saturday in conjunction with the elderly posyandu activities carried out by a team of lecturers and students with posyandu cadres. Activities are given to community groups, especially the elderly who are people with hypertension. A total of 35 elderly people participated in this gymnastics activity. The elderly with hypertension are also very enthusiastic in participating in the elderly gymnastics carried out, as can be seen from the number of participants who participated in gymnastics in this activity. The results of blood pressure monitoring conducted by the community service also showed that there was no significant increase in blood pressure during the implementation of hypertension in most activity participants. Elderly gymnastics activities and blood pressure checks can run very well and the cadres look more enthusiastic and actively involved in activities. This activity is expected to be able to run regularly in the future in collaboration with the puskesmas and posyandu cadres.